Pengaruh Persepsi Harga, Kualitas Produk dan Promosi Terhadap Keputusan Pembelian Konsumen di CV Happy Jaya Plastik Kediri - Raharjo, Gesang Bagus; Nadhiroh, Umi; Wardhani, Rike Kusuma (UNIVERSITAS MARITIM AMNI SEMARANG, 2025)
This study aims to analyze the influence of price perception, product quality, and promotion on consumer purchasing decisions at CV Happy Jaya Plastik Kediri. The research employed a quantitative descriptive approach using a survey method. A total of 96 respondents were selected through purposive sampling, consisting of consumers who had made at least two purchases. Data were collected using a five-point Likert scale questionnaire and analyzed through multiple linear regression using SPSS version 25.0. The results show that both partially and simultaneously, price perception, product quality, and promotion have a positive and significant effect on purchasing decisions. Among these variables, promotion has the most dominant influence, indicating that well-targeted promotional activities can effectively increase consumers’ purchasing intentions and decisions. The coefficient of determination (R²) of 0.781 suggests that these three variables explain 78.1% of the variation in purchasing decisions, while the remaining 21.9% is influenced by other factors outside the model. The findings of this study are expected to serve as a reference for companies in formulating more effective marketing strategies aligned with consumer behavior.